Mis/Representations of Gendered Subalterns and Other Disenfranchised in the Canonical Narratives - Khanal, Niran (The Outlook: Journal of English Studies, 2025)
This paper critiques the representations in the mainstream narratives, The Tempest, Robinson Crusoe and Jane Eyre as they give space to raise questions about the inclusive representations of the marginalized women, slaves and underclass workers. The paper argues that written from the mainstream perspective, these narratives fail to rise above the ideologies of race, gender and class that divide societies. As ideologies influence representations, critiquing them can explore the possibilities for the alternative representations. The narratives of Aime Cesaire, JM Coetzee and Jean Rhys are the instances of such representations. They may not be totally ideal of representations since they have their own limitations. However, there are significant efforts to critique misrepresentations. To examine the points of departures in the alternative narratives regarding representations, the paper has used the comparative approach as a method of study. Moreover, to critique the positions of subalterns and disenfranchised in connection to race, gender and class as projected in the canonical narratives, the study draws the ideas from Gayatri Spivak. The key finding of this paper is that the misrepresentations of the Caribbeans, Africans and other non-Europeans in the mainstream narratives, invite contestations. For instance, Bertha of Jane Eyre as a mad woman, Friday of Robinson Crusoe as a savage, and Caliban of The Tempest as an ugly slave of Prospero question these representations. Therefore, the reproduced critical narratives, Wide Sargasso Sea, Foe and A Tempest respectively redefine the roles of the gendered subalterns and disenfranchised. These narratives envision inclusive and integrative societies where the differences get recognition and the hierarchical relations are bridged by the alternative relations.